Environmental Degradation: Causes and Remediation Strategies 2020
DOI: 10.26832/aesa-2020-edcrs-011
|View full text |Cite
|
Sign up to set email alerts
|

Management and sustainable energy production using flower waste generated from temples

Abstract: Temples are considered as the house of deities. As being a part of their culture, people of Hindu religion pay visits to the temple before starting any auspicious occasion to get blessings of their Gods. Out of them, those who are immense believers of God are the daily visitors of temples. As a part of worship, flowers are essentially used. As a result, a huge amount of flower waste is generated from temples worldwide. The majorly offered flowers in temples include rose, marigold, jasmine, Hibiscus, etc. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Waste disposed of by industries into the environment can increase the transport of potentially toxic elements via water sources [37]. On the other hand, Kankhal is famous for its old temples (Chandi Devi, Mansa Devi, and Daksheswara Mahadev temples); temples generally generate huge loads of tourist and urban wastes, thus leading to infiltration into groundwater reservoirs [38]. Our findings showed that all studied locations were not polluted by natural phenomena or human activities and that lychee production within these regions is, for now, relatively safe.…”
Section: Concentration Of Heavy Metals In Lychee (L Chinensis) Fruit ...mentioning
confidence: 99%
“…Waste disposed of by industries into the environment can increase the transport of potentially toxic elements via water sources [37]. On the other hand, Kankhal is famous for its old temples (Chandi Devi, Mansa Devi, and Daksheswara Mahadev temples); temples generally generate huge loads of tourist and urban wastes, thus leading to infiltration into groundwater reservoirs [38]. Our findings showed that all studied locations were not polluted by natural phenomena or human activities and that lychee production within these regions is, for now, relatively safe.…”
Section: Concentration Of Heavy Metals In Lychee (L Chinensis) Fruit ...mentioning
confidence: 99%
“…Waste produced from temples is mostly organic in nature and form about 70% of entire solid waste (Singh et al, 2018). In India, the amount of floral waste production is 300 million ton per day (Kumar et al, 2020). Temple waste is a heterogeneous mixture of different materials offered to God and its composition varies in each temple.…”
Section: Temple Wastementioning
confidence: 99%
“…Marigold flower waste contains a sufficient amount of nutrients and cellulosic fraction, making it appropriate for a variety of uses, including bioenergy production, dressing for lawn conditioners, compost preparation, and environmentally friendly incense sticks, rose water, and other goods. Hence, marigold-waste-produced cost-effective biofuels have the potential to fulfill sustainable energy demands [19]. As marigold waste offer several high-value products, it develops as a resource rather than merely a waste and exhibits great potential for contributing to a circular bioeconomy once adopted for product extraction before carrying out treatment.…”
Section: Introductionmentioning
confidence: 99%